Exploring the Causalities of Pre-service Teachers’ Perception of Learning Styles Theory - Alan English (The Advocate, 2026)
Prior research has demonstrated Learning Styles Theory’s (LST) wide popularity among K-12 teachers despite a lack of evidence-based support. This study surveyed American pre-service teachers (n = 765) to determine what their perception of LST was, what sources expose them to LST, and how pre-service teachers’ perceptions differed by academic class (freshman through senior). Data analysis suggested that the apprenticeship of observation may impact the continuation of LST and that teacher education programs may not yet be effective at consistently directing pre-service teachers toward research-based alternatives to LST.
Keywords: Learning Styles Theory; Apprenticeship of Observation; K-12 Education; Pedagogy